Liquefied Residue of kenaf core wood produced at different phenol kenaf ratio (Analisis baki pencecairan kayu teras kenaf terhasil pada nisbah Fenol-Kenaf yang berbeza) - Saiful Bahari Bakarudin; Sarani Zakaria; Chin, Hua Chia; Mohd. Jani .S (Universiti Kebangsaan Malaysia, 2012)
Liquefactions of kenaf core wood were carried out at different phenol-kenaf (P/k) ratios. Characterizations of kenaf core wood liquefied residue were carried out to measure the degree of liquefaction. This provides a new approach to understand some fundamental aspects of the liquefaction reaction. Functional groups on the raw kenaf core wood and liquefied residue were examined using Fourier transform infrared spectroscopy (FTIR). The crystallinity index of the kenaf wood liquefied residue, which represents crystallinity changes of the cellulose component after the liquefaction process, was studied using X-ray diffraction (XRD). The surface morphology of the wood residue was observed using scanning electron microscopy (SEM). The thermal behavior of the residues was analyzed using thermogravimetric analysis (TGA). Abroad peak around 3450-3400 cm-1 representing OH stretching in lignin start to disappear as P/K ratio increases. The results showed that the higher the P/K ratio the greater the liquefaction of the lignin component in the kenaf core wood. The crystallinity index (CrI) on the kenaf liquefied residues increased with the increase in P/K ratio. SEM images showed that the small fragments attached on the liquefied kenaf residue surface were gradually removed as the P/K ratio was increased from 1.5/1.0 to 2.5/1.0, which is mainly attributed to the greater chemical penetration toward reactive site of the kenaf fibres. Residue content decreased as the P/K ratio increased from 1.5/1.0 to 2.5/1.0. TGA results showed the increase of heat resistance in the residue as the P/K ratio was increased